Spin-coatable, photopatternable magnetic nanocomposite thin films for MEMS device applications - Kandpal, Manoj; Sharan, C.; Palaparthy, V.; Tiwary, N.; Poddar, P.; Rao, V. Ramgopal (RSC Advances, 2015)
Magnetic nanomaterials' (especially metals) air stability and compatibility with standard micro-fabrication technologies are often a concern for development of MEMS-based magnetic devices. In this paper, we report an air-stable, photo-patternable and spin-coatable magnetic thin film preparation process for MEMS applications. This magnetic nanocomposite thin film was prepared by incorporating carbon capped ferromagnetic cobalt nanoparticles of dimension 20-80 nm into the SU-8 matrix. TEM, XRD and EDAX analyses were done, to investigate the crystal structure, dispersion and phase stability of the films. The SQUID magnetometry and MFM measurements of the film confirmed its magnetic response at room temperature and the retention of its magnetic properties over a period of time. The material compatibility for MEMS device applications was demonstrated through fabrication of a suspended circular membrane of radius similar to 250 mu m, having four U-shaped beams, of dimension similar to 270 x 50 mu m each. Three conventional lithography steps and a sacrificial release layer of similar to 1 mm thick oxide was used for the fabrication. The membrane was characterized by evaluating its spring constant and resonant frequency. The spring constant and resonant frequencies were estimated to be similar to 4.2 N m(-1) and similar to 29 kHz respectively. Finally, we demonstrated the actuation of the magnetic membrane by an off-chip generated magnetic field, for its possible use as a MEMS device.